The Dynamics of the Nggusu Waru Philosophy in Dompu Society, West Nusa Tenggara: Erosion and the Threat of Extinction - Nurhilaliati, Nurhilaliati; Muhammad, Muhammad (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2023)
The philosophy of life, a legacy of values inherited from generation to generation, provides an essential guide to mindset, behavior, and attitude. In the Indonesian context, these philosophies are the main guide in life at the individual and social levels. This study aims to explore the existence of the Nggusu Waru philosophy in Dompu society, involving those from Baby Boomers to Gen-Z. This study employed a qualitative method. The data were collected from observation, document analysis, and interviews. This study revealed a significant decline in the understanding and implementation of the Nggusu Waru philosophy among the Dompu people. Mostly, the local people are no longer familiar with the philosophy, others have limited understanding, and only a small proportion of the Baby Boomer group showed proper understanding and implementation. Factors contributing to this trend include modernization, education, social environment, and the application of traditional values in the contemporary era. This study emphasizes the necessity of preserving, understanding, and reviving traditional values, a major concern for the people of Dompu in West Nusa Tenggara Province.